ANALISIS HUKUM PENYELENGGARAAN SERTIFIKASI HALAL PRODUK UMKM - Nurul Aulina (JURNAL ILMU HUKUM TOPOSANTARO, 2024)
The research method used is empirical normative research which examines primary data and secondary data. Based on the results of the study, that the implementation of halal certification of MSME products in Palu city has not been implemented evenly, because there are several MSME actors who do not yet have halal certificates. Requirements and processes for organizing halal certification of MSME products must be carried out in accordance with the mandate in the JPH Law. Meanwhile, the organizing process is divided into two paths, namely, regular and self-declaration paths. Furthermore, the JPH Law has undergone changes and additions in the Job Creation Law. The changes concern the examination and testing of halal products, deciding fatwas, issuing halal certificates, and labeling. Then, with the latest changes in regulations, the issuance of halal certificates has become the authority of BPJPH, no longer the right of MUI. Adapun metode penelitian yang digunakan yaitu, penelitian normatif empiris yang mengkaji dari data primer dan data sekunder. Berdasarkan hasil penelitian, bahwa penyelenggaraan sertifikasi halal produk UMKM di kota Palu belum terimplementasikan secara merata, dikarenakan ada beberapa pelaku UMKM yang belum memiliki sertifikat halal. Persyaratan dan proses penyelenggaraan sertifikasi halal produk UMKM, wajib dilaksanakan sesuai dengan amanah dalam UU JPH. Adapun, proses penyelenggaranya dibagi menjadi dua jalur yaitu, jalur reguler dan self declare. Selanjutnya, UU JPH mengalami perubahan dan penambahan dalam UU Cipta Kerja. Perubahan itu menyangkut pemeriksaan dan pengujian produk halal, pemutusan fatwa, penerbitan sertifikat halal, dan labelisasi. Kemudian, dengan adanya perubahan aturan terbaru, maka penerbitan sertifikat halal sudah menjadi hak kewenangan BPJPH bukan lagi hak MUI.